Bridging Verbal and Non-Verbal Gaps: Multimodal Presentation Skills at Islamic Higher Education - Fatwassani, Rezza; Hartono, Rudi; Astuti, Puji (Cendekia: Kependidikan dan Kemasyarakatan, 2025)
Effective presentation skills are essential for EFL learners; however, many EFL students struggle to balance verbal proficiency with non-verbal expressiveness, leading to presentations that lack engagement, clarity, and confidence. This study explores how the integration of multimodal communication strategies can bridge the gap between verbal and non-verbal competence in EFL students’ presentations. Using a concurrent embedded mixed-methods design, 17 fourth-semester EFL students were purposively selected from two classes in the teaching Grammar course at Universitas Islam Negeri Walisongo Semarang. Data were collected through classroom observations, video recordings, and questionnaires, and they were analyzed using thematic and descriptive statistical methods. Findings show significant improvements in verbal delivery (pronunciation, fluency, prosody) and non-verbal expression (eye contact, gestures, posture, spatial awareness). Furthermore, it revealed that multimodal strategies enhance presentation quality and reduce language anxiety by distributing communicative load across multiple modes. It recommends embedding multimodal training in EFL curricula with constructive feedback and accessible digital tools.